2002
DOI: 10.1002/tcr.10028
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Some Alkyl Substituted Phthalocyanines and Related Macrocycles

Abstract: This report provides an account of research undertaken at the University of East Anglia, United Kingdom, into phthalocyanine derivatives substituted at six or more of the nonperipheral sites by alkyl groups. When first prepared they were only the second series of substituted phthalocyanines known to exhibit columnar liquid crystal behaviour. The compounds also form structured films by the spin-coating technique, a formulation with potential for FET devices. The zinc metallated derivatives are photosensitisers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…[16] This behaviour has been ascribed to the combined effect of the mutual steric interference of the nonperipheral side chain and the modulation of the attractive p--p intermolecular interactions as a result of the electron-donating effect of the eight oxygen atoms directly attached to the macrocycle. [1,17,21,32] Based on the clearing temperatures of the hexagonal columnar mesophase of the members of series 1, 3 and 5 (Figure 3), it can be concluded that the strategy of reducing phthalocyanine cofacial association by attaching alkyl chains to a five-membered carbon ring fused to the periphery of the macrocycle (series 5) is no more efficient than the direct attachment of the chains at the peripheral sites (series 1). Indeed, by placing the alkyl chains at the nonperipheral sites (series 3), a much greater destabilising effect on the thermal stability of the columnar mesophase appears to be induced.…”
Section: Discussionmentioning
confidence: 99%
“…[16] This behaviour has been ascribed to the combined effect of the mutual steric interference of the nonperipheral side chain and the modulation of the attractive p--p intermolecular interactions as a result of the electron-donating effect of the eight oxygen atoms directly attached to the macrocycle. [1,17,21,32] Based on the clearing temperatures of the hexagonal columnar mesophase of the members of series 1, 3 and 5 (Figure 3), it can be concluded that the strategy of reducing phthalocyanine cofacial association by attaching alkyl chains to a five-membered carbon ring fused to the periphery of the macrocycle (series 5) is no more efficient than the direct attachment of the chains at the peripheral sites (series 1). Indeed, by placing the alkyl chains at the nonperipheral sites (series 3), a much greater destabilising effect on the thermal stability of the columnar mesophase appears to be induced.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that this type of substituted compound has satisfactory solubility in most common solvents and forms well-ordered spin-coated films as judged by low-angle x-ray reflectivity measurements [32,33]. These investigations also indicate that during the evaporation process the molecules assemble into layers of columns whose axes are parallel to the surface of the substrate [34]. The control of the interface between the organic active layer and the gate dielectric layer is important for realization of faster transistors with low threshold voltages.…”
Section: Introductionmentioning
confidence: 96%
“…The binuclear complex displayed a positive nonlinear absorption coefficient. It is found that the linear optical properties were little changed but the optical limiting effectiveness of the binuclear fused phthalocyanine 1 is lower relative to tBu 4 The versatility of Pc synthetic organic chemistry [21,22] has led to a large variety of Pc structures differing in the number, nature and position of peripheral substituents, [23][24][25][26][27] with various coordinating central atoms, [17] axial ligands, [28,29] and with a variable number of linkages between Pc rings in oligomeric [30,31] or polymeric species. [32] Among the many possibilities for varying the Pc structure, the expansion of the π-electron system through the synthesis of naphthalocyanines (Ncs) is the most common.…”
Section: Introductionmentioning
confidence: 99%